Control of Study Activity as an Important Factor in The Formation of Intellectual and Cognitive Competencies of Primary School Students (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article highlights the importance of educational activity control in the formation of intellectual and cognitive competences of students of junior school age.